Analysis of customer experience in a Singapore SME : a business case of Sulpa Office Supplies Pte Ltd. - Ngeng, Shu Wen. (2011)
To differentiate one supplier from another, additional dimensions are required within the proposition: some use price and contract terms - and the smart ones use customer experience (CE) (Hollyoake, 2009). This case paper demonstrates the use of CE constructs to understand, analyze and propose strategies in a Singapore SME.